Kontribusi Dukungan Orang Tua Dalam Layanan Konsultasi Bimbingan Dan Konseling - Prayoga Prayoga; Jesicca Wulandari; Muthia Fauziyyah Andini; Sri Chantika Putri Zalianti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to find out how parental involvement influences the provision of guidance and counseling consultation services. Family is the first and most important social environment for a child. Parental guidance, love, and supervision can contribute to the development of children's self-confidence and academic success. To deal with children's problems effectively, counselors, educators and parents must work synergistically. An additional strategy to encourage this collaboration is to offer parent consultation services. This can help parents strengthen their bonds with their children, offer wise guidance, and realize the impact of love on family growth. To increase collaboration between counselors, educators and parents in dealing with children's problems, it can be concluded that parent consultation services are an important strategy.